Winding Number Selection on Merons by Gaussian Curvature’S Sign - Elias-Moreno, R; Vidal-Silva, N (Nature Publishing Group, 2019)
We study the relationship between the winding number of magnetic merons and the Gaussian curvature of two-dimensional magnetic surfaces. We show that positive (negative) Gaussian curvatures privilege merons with positive (negative) winding number. As in the case of unidimensional domain walls, we found that chirality is connected to the polarity of the core. Both effects allow to predict the topological properties of metastable states knowing the geometry of the surface. These features are related with the recently predicted Dzyaloshinskii-Moriya emergent term of curved surfaces. The presented results are at our knowledge the first ones drawing attention about a direct relation between geometric properties of the surfaces and the topology of the hosted solitons. © 2019, The Author(s).